2016
DOI: 10.1021/acs.energyfuels.6b01519
|View full text |Cite
|
Sign up to set email alerts
|

Acylamide and Amine Oxide Derivatives of Linear and Hyperbranched Polyethylenimine. Part 2: Comparison of Gas Kinetic Hydrate Inhibition Performance

Abstract: A series of acylamide and amine oxide derivatives of polyethyleneimine, both hyperbranched (HPEI) and linear (LPEI), have been synthesised and their performance as kinetic hydrate inhibitors (KHIs) with a Structure II-forming natural gas mixture investigated in high pressure steel rocking cell experiments. This is the first time the KHI performance of linear and polymers of with the same functional groups have been compared. The importance of quality control in KHI synthesis is also highlighted.In general the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The amine oxide group (NO, also written as N + –O – ) is highly hydrophilic as a result of its strong polarity, and it also possesses three covalent bonds for connecting with hydrophobic groups. Recently, studies showed that amine oxide compounds can perform well as KHIs, which was demonstrated for linear or hyperbranched alkylated ethylene–amine oxides. In addition, the amine oxide group has been proven to be rather biocompatible, which meets the criteria of designing environmentally friendly KHIs. , Thus, further investigation of amine oxide-containing polymers as KHIs is of particular interest, which motivated the studies presented here.…”
Section: Introductionmentioning
confidence: 93%
“…The amine oxide group (NO, also written as N + –O – ) is highly hydrophilic as a result of its strong polarity, and it also possesses three covalent bonds for connecting with hydrophobic groups. Recently, studies showed that amine oxide compounds can perform well as KHIs, which was demonstrated for linear or hyperbranched alkylated ethylene–amine oxides. In addition, the amine oxide group has been proven to be rather biocompatible, which meets the criteria of designing environmentally friendly KHIs. , Thus, further investigation of amine oxide-containing polymers as KHIs is of particular interest, which motivated the studies presented here.…”
Section: Introductionmentioning
confidence: 93%
“…Reports showed that hyperbranched polyethylenimine-alkyl-amine N-oxides (HPEI-R-AOs), especially those with large alkyl groups, can inhibit the formation of both sI and sII hydrates effectively. 17,22 Lately, Zhang et al reported that poly(piperidine glycidyl amine N-oxide) (PIGAO) showed considerable KHI performance on sII hydrate. The best results were on par with the highly established commercial PVCap.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, several series of nonamide polymers, such as poly­(isopropenyloxazoline), poly­(vinylphosphonate) diesters, poly­(alkyl ethylene phosphonate)­s, poly­(amine N -oxide)­s, poly­(vinylsulfonamide)­s, poly­(vinylaminal)­s, poly­(sulfobetaine methacrylate)­s, and polysaccharides like starch, chitosan, and pectin, have been reported to be excellent KHIs (Figure ). Poly­(amine N -oxide) nonamide KHIs have attracted increasing attention, due to the immense structural variability, their superior hydrophilicity, and, most importantly, the remarkable inhibition performance of amine N -oxide polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few examples of direct synthesis of KHIs from polymers such as hyperbranched polyethylenimines that form hyperbranched polyethylenimine-alkyl-amine oxides. , Therefore, we wondered if we could access KHI polymers based on the active monomers directly from more widely available polymeric starting materials. This would avoid using the more expensive acrylamido monomers in Figure and could possibly reduce the cost of (meth)­acrylamido-based KHI polymers.…”
Section: Introductionmentioning
confidence: 99%